Conspiracy narratives and vaccine hesitancy: a scoping review of prevalence, impact, and interventions - Frederike Taubert; Georg Meyer-Hoeven; Philipp Schmid; Pia Gerdes; Cornelia Betsch (BMC, 2024)
Abstract Believing conspiracy narratives is frequently assumed to be a major cause of vaccine hesitancy, i.e., the tendency to forgo vaccination despite its availability. In this scoping review, we synthesise and critically evaluate studies that assess i) the occurrence of vaccine-related conspiracy narratives on the internet, ii) the prevalence of belief in vaccine-related conspiracy narratives, iii) the relationship between belief in conspiracy narratives and vaccination intention or vaccination uptake, and iv) interventions that reduce the impact of conspiracy narratives on vaccination intention. In July 2022, we conducted a literature search using three databases: PubMed, PsychInfo, and Web of Science. Following the PRISMA approach, of the 500 initially identified articles, 205 were eligible and analysed. The majority of identified studies were conducted in Europe and North America, were published in 2021 and 2022, and investigated conspiracy narratives around the COVID-19 vaccination. The prevalence of belief in various vaccine-related conspiracy narratives varied greatly across studies, from 2 to 77%. We identified seven experimental studies investigating the effect of exposure to conspiracy narratives on vaccination intentions, of which six indicated a small negative effect. These findings are complemented by the evidence from over 100 correlative studies showing a significant negative relationship between conspiracy beliefs and vaccination intention or uptake. Additionally, the review identified interventions (e.g., social norm feedback, fact-checking labels, or prebunking) that decreased beliefs in vaccine-related conspiracy narratives and, in some cases, also increased vaccination intentions. Yet, these interventions had only small effects. In summary, the review revealed that vaccine-related conspiracy narratives have spread to varying degrees and can influence vaccination decisions. Causal relationships between conspiracy beliefs and vaccination intentions remain underexplored. Further, the review identified a need for more research on interventions that can reduce the impact of conspiracy narratives.